Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1526-4610.2002.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Circadian Rhythmicity of Nociceptive Reflex Threshold in Cluster Headache

Abstract: Our findings suggest that in cluster headache there may be impairment of the pain control system that is associated with periodic failure of the mechanisms involved in the organization of biological rhythms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
(116 reference statements)
3
25
0
Order By: Relevance
“…Of the 11 studies that did report results, seven were consistent with the broader results of this review, two studies were opposing, and the remaining two were similar but with important albeit subtle differences (see Table 2 for details). The most prominent inconsistencies were those related to reflex thresholds: one study reported no difference in NFR thresholds between people with chronic low back pain or acute postoperative pain and pain-free controls (Peters et al, 1992), and the other reported no difference in NFR threshold between patients with chronic cluster headache and healthy controls (Nappi et al, 2002). The latter study (Nappi et al, 2002) had a medium risk of bias, which decreases our confidence in the results, but the former (Peters et al, 1992) had only a low risk of bias.…”
Section: Studies Not Included In the Meta-analysesmentioning
confidence: 95%
See 3 more Smart Citations
“…Of the 11 studies that did report results, seven were consistent with the broader results of this review, two studies were opposing, and the remaining two were similar but with important albeit subtle differences (see Table 2 for details). The most prominent inconsistencies were those related to reflex thresholds: one study reported no difference in NFR thresholds between people with chronic low back pain or acute postoperative pain and pain-free controls (Peters et al, 1992), and the other reported no difference in NFR threshold between patients with chronic cluster headache and healthy controls (Nappi et al, 2002). The latter study (Nappi et al, 2002) had a medium risk of bias, which decreases our confidence in the results, but the former (Peters et al, 1992) had only a low risk of bias.…”
Section: Studies Not Included In the Meta-analysesmentioning
confidence: 95%
“…The most prominent inconsistencies were those related to reflex thresholds: one study reported no difference in NFR thresholds between people with chronic low back pain or acute postoperative pain and pain-free controls (Peters et al, 1992), and the other reported no difference in NFR threshold between patients with chronic cluster headache and healthy controls (Nappi et al, 2002). The latter study (Nappi et al, 2002) had a medium risk of bias, which decreases our confidence in the results, but the former (Peters et al, 1992) had only a low risk of bias. Other studies reporting findings inconsistent with the meta-analysis include AlAzzawi et al (2008), who reported delayed blink reflex latencies in people with rheumatoid arthritis than in healthy controls and Neziri et al (2010), who reported a higher reflex amplitude in people with chronic endometriosis than healthy controls.…”
Section: Studies Not Included In the Meta-analysesmentioning
confidence: 95%
See 2 more Smart Citations
“…83,84 Impaired pain perception with decreased pain thresholds due to a dysfunction of pain control systems might also have a role in cluster headache. 85 Preliminary data from a functional imaging report of a patient suffering a spontaneous cluster headache attack provided some evidence for periaqueductal grey matter activation during attacks, 25 a brain area crucial for endogenous pain control. Moreover, a decreased metabolism in frontal brain circuits, which might be important in top-down modulation of pain processing, was recently demonstrated.…”
Section: Migrainementioning
confidence: 99%